Pengaruh Komitmen Organisasi, Tingkat Keseriusan Kecurangan, Intensitas Moral Dan Lingkungan Etika Terhadap Niat Melakukan Whistleblowing (Studi Kasus Pada Dinas Pendidikan Provinsi Riau) - Rika Novriyanti; Rama Gita Suci; Annie Mustika Putri (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2025)
This study aims to analyze the effect of organizational commitment, the seriousness of fraud, moral intensity and ethical environment on the intention to do whistleblowing in the Riau Provincial Education Office. Whistleblowing is an important mechanism in disclosing fraudulent acts that can harm organizations and society. This study uses a quantitative approach with a survey method through a questionnaire distributed to 261 employees. The sampling technique in the study used a saturated sampling technique method in which all populations were used as samples, so that a total sample size of 261 respondents was obtained. This research was processed using SPSS 25. Data were analyzed using multiple linear regression to test the relationship between variables. The results of this study indicate that organizational commitment, the seriousness of fraud, and moral intensity have a significant effect on whistleblowing intentions. However, the ethical environment has no effect on whistleblowing intentions. This shows that individuals who have a high commitment to the organization, assess fraud as serious, and have strong moral intensity, are more likely to do whistleblowing. In contrast, the ethical environment in the organization does not directly encourage the intention to report fraud.